2017
DOI: 10.1111/myc.12733
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new fluorescent reagent, fluorescent brightener 85, for the diagnosis of suspected onychomycosis compared with potassium hydroxide

Abstract: Onychomycosis is a common fungal infection in dermatology clinics. The commonly used diagnostic method, potassium hydroxide (KOH) direct microscopy, does not have a high-positive detection rate. Therefore, a new diagnostic method is needed to confirm onychomycosis. The objective of this research was to use fluorescent brightener 85 (FB 85), a new fluorescent reagent for fungi detection, and to evaluate this new method based on the diagnostic positive rate, accuracy and efficiency in suspected onychomycosis com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Although routinely performed, 10% KOH smear has rather low sensitivity and specificity. The sensitivity and specificity of 10% KOH smear in the diagnosis of OC have been reported to be 9.67% ~ 73.3% and 36.6% ~ 48.6%, respectively (Levitt, Levitt, Akhavan, & Yanofsky, 2010;Lyu, Zhao, Yan, & Hua, 2016;Marty, Bourrat, Vaysse, Bonner, & Bailleul-Forestier, 2015;Yue, Wang, Wang, Li, & Yue, 2018). Furthermore, other smear methods, such as Gram staining and periodic acid-Schiff (PAS) staining, are not suitable for clinical rapid diagnosis due to complicated and long time-consuming operation (Lyu et al, 2016;Yao, Shi, Zhang, Sun, & Wu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although routinely performed, 10% KOH smear has rather low sensitivity and specificity. The sensitivity and specificity of 10% KOH smear in the diagnosis of OC have been reported to be 9.67% ~ 73.3% and 36.6% ~ 48.6%, respectively (Levitt, Levitt, Akhavan, & Yanofsky, 2010;Lyu, Zhao, Yan, & Hua, 2016;Marty, Bourrat, Vaysse, Bonner, & Bailleul-Forestier, 2015;Yue, Wang, Wang, Li, & Yue, 2018). Furthermore, other smear methods, such as Gram staining and periodic acid-Schiff (PAS) staining, are not suitable for clinical rapid diagnosis due to complicated and long time-consuming operation (Lyu et al, 2016;Yao, Shi, Zhang, Sun, & Wu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the author Yue's 23 another study, she was the first to use FB 85 to evaluate the accuracy and efficiency for the diagnosis of onychomycosis in clinic and found that FB 85 had a higher positive rate than the KOH method, which had a statistically significant difference. However, in our study, both the FB 85 and KOH methods had similar positive rates and had no statistical significance difference.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 , 21 , 22 However, no study has used CFW for the diagnosis of VVC. Moreover, fluorescent brightener 85, a new fluorescent reagent, was first found and used for the diagnosis of onychomycosis by the author, 23 but there is no research about using FB 85 to detect fungi in VVC.…”
Section: Introductionmentioning
confidence: 99%
“…Our study introduces Fluorescent Brightener 85 (FB 85), a compound traditionally used in laundry detergents, for detecting fungal elements in clinical diagnostics by the author Yue. This repurposing, validated by Yue's recent work in onychomycosis and vulvovaginal candidiasis (VVC) detection [18,20], led to the patenting of FB 85 as a national invention. Given its preliminary success, this study aims to further evaluate FB 85's effectiveness across a broader spectrum of fungal infections and different cultured fungi, and in super cial fungal infection samples in a clinical setting, demonstrating its potential as a novel clinical uorescent reagent.…”
Section: Introductionmentioning
confidence: 99%